School-University Partnerships in Action: Concepts, Cases and Concerns - Susan Day Harmison (Educational Considerations, 1988)
A book review of School-University Partnerships in Action: Concepts, Cases and Concerns, edited Kenneth A. Sirotnik and John I. Goodlad.